How Good Is Goodwill Accounting? Comparative Evidence on Post-FAS 141(R) Acquired Intangibles Accounting - Beatty, Anne; Liao, Scott; Weber, Joseph P. (The Accounting Review, 2026)
ABSTRACT Concerns that goodwill impairments unresponsiveness to declining performance produces inflated goodwill led standard-setters to reconsider post-acquisition impairment-only accounting. We use granular large-scale data to provide institutionally relevant novel descriptive evidence motivated by this hotly debated accounting standard. Comparing goodwill versus other acquired intangibles growth rates for firms reporting goodwill throughout the 2010–2020 post-FAS 141(R) period provides no evidence of runaway goodwill inflation concerns. For firms with goodwill anytime during 2010–2020 we use Shapley values to explore the explanatory power of performance factors affecting goodwill impairments. Consistent with standard-setters’ intent, single-segment market performance explains 81 percent of goodwill impairment incidence variation (controlling for Fama-French-38 industry and time fixed-effects). Limited evidence of reduced impairment incidence after incorporating FASB sanctioned control premia or alternative market values provides little support for discretionary impairment avoidance. Conversely, higher impairment incidence when book values incorporate IFRS (2020) proposed off-balance-sheet headroom or market-to-book decreases supports discretionary impairment recognition. Data Availability: The data used in this study are obtained from commercial sources, including Compustat, Calcbench, I/B/E/S, FactSet Mergerstat/BVR, and Peters and Taylor's intangible capital dataset. JEL Classifications: M41; M48; G34.